Chromiteen: A New 2D Oxide Magnetic Material from Natural Ore. Issue 19 (8th July 2018) - Yadav, Thakur Prasad; Shirodkar, Sharmila N.; Lertcumfu, Narumon; Radhakrishnan, Sruthi; Sayed, Farheen N.; Malviya, Kirtiman Deo; Costin, Gelu; Vajtai, Robert; Yakobson, Boris I.; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract: The absence of inherent magnetism in the family of 2D materials limits its application in magnetoelectric and magnetic storage media. Here, a simple scalable route for the synthesis of magnetic 2D material chromite (chromiteen) via sonication‐assisted liquid‐phase exfoliation is demonstrated. The (111) plane of the exfoliated chromite is found to be the most stable which is confirmed by its common occurrence in exfoliation. Further, the stability and dispersion are verified by ab initio density functional theoretical simulations. Magnetic measurements over a large temperature range of 4 K  ≤   T   ≤  300 K confirm ferromagnetic/superparamagnetic order with nearly 40 times higher magnetic moment saturation in chromiteen compared to chromite. The results reveal that 2D chromiteen causes a change in the magnetic behavior with respect to chromite which could be ascribed to the increase in the lattice strain as well as a magnetic strain due to high ferromagnetic fraction in 2D plane. Abstract : The synthesis of magnetic 2D material "chromiteen" from natural ore chromite via sonication‐assisted liquid‐phase exfoliation. Ferromagnetic/superparamagnetic order in chromiteen is nearly 40 times higher compared to chromite due to the increase in the lattice strain as well as a magnetic strain due to high ferromagnetic fraction in 2D plane.